Pengaruh Pengalaman Belanja Online Dan Kepercyaan Terhadap Minat Beli Ulang Di Tiktok Shop (Studi Kasus Mahasiswa Fkip Uhamka 2018) - Silvia Dwi Yanti; Sri Astuti; Camelia Safitri (Jurnal EMT KITA, 2023)
The internet has grown rapidly, thus making online shopping service providers such as TikTok Shop have to modify several ways in order to compete with other e-commerce competitors. This study aims to analyze the effect of shopping experience and consumer trust on repurchase interest in the TikTok Shop application, the study was conducted on FKIP UHAMKA students class 2018. The research method used was quantitative research with non-probability sampling technique and obtained a sample of 70 respondents. The data was collected using a questionnaire and then analyzed using multiple linear regression and the data was processed with the help of the JASP (Jeffreys’s Amazing Statistic Program) statistical application. The results showed that the online shopping experience had a significant positive effect on repurchase interest with a value of sig 0.001 <0.05, while the trust variable had no significant effect on repurchase interest with a sig value of 0.076> 0.05. Simultaneously, online shopping experience and trust affect repurchase intention with a value of sig 0.001 < 0.05. It is important for Tiktok Shop managers to maintain consumer confidence in order to increase consumer surplus every year.